Decolonizing Sustainability: Integrating Islamic Legal Pluralism into Post-2030 Agendas - Muhammad jibril, Abubakar (Fakultas Hukum Universitas Islam Jakarta, 2025)
The international sustainability agenda, founded upon the UN 2030 Sustainable Development Goals and subsequent COP climate agreements, is ever more reproached for institutionalizing colonial technocratic frameworks that sideline local epistemologies. This research formulates a decolonial approach to incorporate Islamic legal pluralism, specifically Maliki fiqh ideals and Quranic khalīfah (stewardship), mīzān (balance), and fasād (corruption) concepts into post‑2030 sustainability agendas in Nigeria. Using a qualitative doctrinal and document-based method, we examine primary legal texts (the Nigerian Land Use Act; state Sharia codes), classical fiqh texts, international policy documents, and grey literature, including religious declarations. We find that Islamic institutions (waqf endowments, zakat councils, Sharia courts) are communal governance structures embracing environmental stewardship and social justice, yet under-engaged in national policy. We trace pathways for legal reform, such as the amendment of land tenure legislation to protect waqf lands, and institutional innovation, such as